THE TRANSITION TO AN INNOVATIVE ECONOMY AS A STRATEGIC IMPERATIVE - Nurtdinov, Ravil M.; Nurtdinov, Albert R.; Gabdrakhmanov, Niyaz K. (Gênero & Direito, 2019)
This paper discusses innovation as the key to economic growth, an assessment of the innovation sphere, and justified way innovative activities of economic subjects. The experience of industrialized countries shows conclusively that sustained economic growth in modern conditions is not the result of primitive production capacity factors, but their improvement and development on the basis of scientific and technological progress and innovation. To examine the strategy of Russia’s development we must take into account that new trends fundamentally alter our understanding of the mechanisms of economic growth. Russia must solve both its tactical problems and seek answers to new challenges in order to ensure gradual, phased transition from the old inertial, natural-resource growth model to a predominantly innovative type of development. In this article as a hypothesis put forward the following points: innovation sphere Russia is experiencing a deep crisis; the key problem in the way of innovation activity in the country is the lack of effective mechanisms for funding research and development